2021
DOI: 10.1097/sla.0000000000004840
|View full text |Cite
|
Sign up to set email alerts
|

High-risk Pancreatic Anastomosis Versus Total Pancreatectomy After Pancreatoduodenectomy

Abstract: Objective: To evaluate TP as an alternative to PD in patients at high-risk for popf. Background: Outcomes of high-risk PD (HR-PD) and TP have never been compared. Methods: All patients who underwent PD or TP between July 2017 and December 2019 were identified. HR-PD was defined according to the alternative fistula risk score. Postoperative outcomes (primary endpoint), pancreatic insufficiency, and quality of life after 12 months of follow-up (QoL) were compared between HR-PD or planned PD intraoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 41 publications
4
56
0
7
Order By: Relevance
“…16 The national database from the American College of Surgeons revealed higher major morbidity and a doubled 30-day mortality rate (6% vs. 3%) after TP in comparison to PD. 39 In contrast, others demonstrated comparability 8,[13][14][15]18,40,41 in major morbidity (19-30% vs. 26-37%) 8,14,18,19 and perioperative mortality (0-7% vs. 0-5%) 8,[13][14][15]18,19,41 from which four studies matched both groups. [13][14][15]18 One single-center study compared TP versus PD with high-risk PJ (Fistula Risk Score 7-10), revealing no differences in major morbidity, 17 whereas Luu et al compared TP indicated for high-risk pancreatic remnant versus high-risk PD, demonstrating comparable major morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The national database from the American College of Surgeons revealed higher major morbidity and a doubled 30-day mortality rate (6% vs. 3%) after TP in comparison to PD. 39 In contrast, others demonstrated comparability 8,[13][14][15]18,40,41 in major morbidity (19-30% vs. 26-37%) 8,14,18,19 and perioperative mortality (0-7% vs. 0-5%) 8,[13][14][15]18,19,41 from which four studies matched both groups. [13][14][15]18 One single-center study compared TP versus PD with high-risk PJ (Fistula Risk Score 7-10), revealing no differences in major morbidity, 17 whereas Luu et al compared TP indicated for high-risk pancreatic remnant versus high-risk PD, demonstrating comparable major morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…16 Three studies specified this comparison to PD with high-risk conditions, noticing the potential of TP to improve perioperative outcomes. [17][18][19] Quality of life (QoL) was investigated by only one of them, revealing comparable outcomes. 19 This study aims to investigate the clinical value of TP as an alternative to PD with a high-risk PJ to reduce short-term morbidity and mortality, thereby investigating the impact on long-term QoL.…”
Section: Introductionmentioning
confidence: 99%
“…TP is indicated in cases of diffuse MPD involvement, multifocal disease in patients with family history positive for PDAC, and persistent HGD at the resection margin because the established risk for recurrence and/or cancer in these patients makes the morbidity of TP more acceptable [52]. Moreover, recent studies have reported improved perioperative outcomes and postoperative quality of life (QoL) after TP, presumably due to centralization at high-volume centers and development of long-acting insulin and modern pancreatic enzyme preparations [53][54][55][56][57].…”
Section: Surgery For Ipmns: Intra-and Postoperative Implicationsmentioning
confidence: 99%
“…Unfortunately, data exploring this topic are sparse and come solely from recently published studies [ 8 , 16 ]. Far from advocating the systematic use of TP in high-risk scenarios, we think that it may be considered as an alternative to perform a high-risk pancreatic anastomosis in highly selected patients for whom the short-term benefits in the postoperative setting may overcome the disadvantages due to the complete absence of residual pancreatic function.…”
Section: Total Pancreatectomy To Avoid Pancreatic Fistula In High-risk Patients: a Promising New Friend?mentioning
confidence: 99%
“…In this perspective, the encouraging postoperative outcomes of total pancreatectomy (TP) reported at high-volume centers in recent years [ 6 , 7 ] have led the authors questioning whether the burden of complications related to a high-risk pancreatic anastomosis could justify the use of TP as an alternative strategy in selected patients to avoid the occurrence of POPF [ 8 ].…”
Section: Introductionmentioning
confidence: 99%